2013
DOI: 10.1007/s00705-013-1626-6
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Hsc70, PDI and integrin αvβ3 involvement during entry of the murine rotavirus ECwt into small-intestinal villi of suckling mice

Abstract: In the present study, a homologous rotavirus, ECwt, infecting small intestinal villi isolated from ICR and BALB/c mice were used as a model for identifying cell-surface molecules involved in rotavirus entry. Small-intestinal villi were treated with anti-Hsc70, anti-PDI, anti-integrin β3 or anti-ERp57 antibodies or their corresponding F(ab')2 fragments before inoculation with rotavirus ECwt, RRV or Wa. Pretreatment of villi decreased virus infectivity by about 50-100 % depending of the rotavirus strain, antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…Similarly, thiol groups are generated in the outer capsid proteins after TLPs contact the cell surface, suggesting that PDI or other related thioredoxins are able to reduce disulfide bonds in viral proteins (Rivera M, Guerrero CA, Acosta O, manuscript in preparation). Studies characterizing potential cell surface receptors for rotavirus infection of small intestinal villus cells from mice showed that raft-associated Hsc70, PDI and integrin β3 played an important role in the rotavirus entry process as previously shown for MA104 cells [127] . It has been reported that integrin subunit β3 and integrin α2β1 are present on the cell surface of murine and human enterocytes [157,158] , and that rotavirus-susceptible MA104, COS7 and Caco-2 cells also contain cell surface receptors including αvβ3 and Hsc70 [113,128] .…”
Section: Dlp-tlp Inter-conversionsupporting
confidence: 56%
See 3 more Smart Citations
“…Similarly, thiol groups are generated in the outer capsid proteins after TLPs contact the cell surface, suggesting that PDI or other related thioredoxins are able to reduce disulfide bonds in viral proteins (Rivera M, Guerrero CA, Acosta O, manuscript in preparation). Studies characterizing potential cell surface receptors for rotavirus infection of small intestinal villus cells from mice showed that raft-associated Hsc70, PDI and integrin β3 played an important role in the rotavirus entry process as previously shown for MA104 cells [127] . It has been reported that integrin subunit β3 and integrin α2β1 are present on the cell surface of murine and human enterocytes [157,158] , and that rotavirus-susceptible MA104, COS7 and Caco-2 cells also contain cell surface receptors including αvβ3 and Hsc70 [113,128] .…”
Section: Dlp-tlp Inter-conversionsupporting
confidence: 56%
“…It has been reported that integrin subunit β3 and integrin α2β1 are present on the cell surface of murine and human enterocytes [157,158] , and that rotavirus-susceptible MA104, COS7 and Caco-2 cells also contain cell surface receptors including αvβ3 and Hsc70 [113,128] . The colocalization of PDI, integrin β3, Hsc70 and rotavirus particles in lipid microdomains (rafts) from MA104 and intestinal villus cells [12,127] suggest that PDI reducing function at cell surface can activate either integrins or VP7 to interact each other during entry [94] . The role of thiol-disulfide exchange during rotavirus infection is well documented, but the detailed processes of this implication still remain incompletely elucidated.…”
Section: Dlp-tlp Inter-conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Hsp related to S. aureus internalization in NPPCs is Hsc70. This protein is associated with viral infections by acting as a receptor for human T-cell lymphotropic virus type 1 (HTLV-1) [64] or rotaviruses [65, 66]. Hsc70 interacts with S. aureus hydrolases such as autolysin (Atl) during the bacterial internalization process.…”
Section: Heat Shock Proteinsmentioning
confidence: 99%